POLITIK PEMUSNAHAN DAN PEMUSNAHAN POLITIK : Telaah Kritis Atas Konsep Hannah Arendt Tentang Totalitarisme - Mathias Daven (Jurnal Ledalero, 2015)
If we wish to understand a totalitarian system as a whole, we need first to understand the central role of the concentration camp as a laboratorium to experiment in total domination. Arendt’s analysis of totalitarianism in the twentieth century shows how a totalitarian regime cannot survive without terror; and terror will not be effective without concentration camps. Experiments in concentration camps had as their purpose, apart from wiping out any freedom or spontaneity, the abolishing of space between human beings, abolishing space for politics. Thus, totalitarianism did not mirror only the politics of extinction, but also the extinction of politics. As a way forward, Arendt analyses political theory that forces the reader to understand power no longer under the rubric of domination or violence – although this avenue is open – but rather under the rubric of freedom. Arendt is convinced that the life of a destroyed nation can be restored by mutual forgiveness and mutual promises, two abilities rooted in action. Political action, as with other acts, is identical with the ability to commence something new. Keywords: Totalitarisme, antisemitisme, imperialisme, dominasi, teror, kebebasan, kedaulatan, kamp konsentrasi, politik, ideologi, tindakan